The Average Stellar Population Age and Metallicity of Intermediate-redshift Quiescent Galaxies - Ivana Damjanov; Margaret J. Geller; Jubee Sohn (The Astrophysical Journal)
The HectoMAP spectroscopic survey provides a unique mass-limited sample of more than 35,000 quiescent galaxies ( D _n 4000 > 1.5) covering the redshift range 0.2 <  z  < 0.6. We segregate galaxies in bins of properties based on stellar mass, D _n 4000, and redshift to construct a set of high signal-to-noise spectra representing a massive ( M _*  > 10 ^10 M _⊙ ) quiescent population at intermediate redshift. These high-quality summed spectra enable full spectrum fitting and the related extraction of the average stellar population age and metallicity. The average galaxy age increases with the central D _n 4000 as expected. The correlation is essentially invariant with stellar mass; thus, D _n 4000 is a robust proxy for quiescent galaxy stellar population age. HectoMAP provides the first quiescent sample at intermediate redshift comparable with z  ∼ 0 mass-complete data sets. Scaling relations derived from the HectoMAP summed spectra connect stellar age and metallicity with quiescent galaxy stellar mass up to z  ∼ 0.5. Anticorrelation between the equivalent width (EW) of the [O ii ] emission line and stellar age, together with the mild increase in stellar age with stellar mass, supports a broad range of timescales for the mass assembly of intermediate-redshift quiescent systems. On average, the most massive galaxies ( M _*  > 10 ^11 M _⊙ ) assemble the bulk of their stars at earlier epochs. A strong increase in the average stellar metallicity with stellar mass, along with the correlation between the [O ii ] EW and metallicity at 0.2 <  z  < 0.4, suggests that lower mass galaxies are more likely to have experienced recent star formation episodes; related feedback from massive stars affects the chemical enrichment of these galaxies.